A Comparative Analysis of Post Restructuring Performance of Firms in Financial and Real Sectors in Nigeria - J.A, Oloyede; L.A, Sulaiman (Asian Journal of Empirical Research, 2013)
This study carries out a comparative analysis of post restructuring performance of firms in the financial sector proxy by banks and real sector proxy by the firms in the oil and gas industry and to see if corporate restructuring affects the performance of firms selected from the banking sector as well as oil and gas sector in Nigeria. It also tries to see if the post restructuring performance also varies in these sectors. A sample of Ten (10) banks were randomly chosen from the list of quoted banks after the restructuring exercise and four (4) firms that had restructured their operations were drawn from the Oil and Gas sector. Data were collected from the NSE Factbook and Annual Statement of Account and Reports of the Firms. The study covers 2000 – 2011. Financial ratios and‘t’ test were calculated and compared for a period of 3 years before restructuring and 3 years after restructuring for firms in each sector. The study discovers that restructuring has significant effect on the profitability, liquidity and solvency of firms in real sectors and that restructuring does not have any significant effect on firms in the financial sector. It recommends that Management should instill discipline upon itself by ensuring good corporate governance, promote technological progress, and increase its paid up capital regardless of the statutory requirements so that the continued existence of the firm is not jeopardized.